The Cell Cycle Inhibitors p21 Cip1 and p27 Kip1 Control Proliferation but Enhance DNA Damage Resistance of Glioma Stem Cells - Morris Hanon, Olivia (2017)
High-grade gliomas are the most prevalent and lethal primary brain tumors. They display a hierarchical arrangement with a population of self-renewing and highly tumorigenic cells called cancer stemcells. These cells are thought to be responsible for tumor recurrence, which make them main candidates for targeted therapies. Unbridled cell cycle progression may explain the selective sensitivity of some cancer cells to treatments. The members of the Cip/Kip family p21Cip1 and p27Kip1 were initially considered as tumor suppressors based on their ability to block proliferation. However, they are currently looked at as proteins with dual roles in cancer: one as tumor suppressor and the other asoncogene. Therefore, the aimof this study was to determine the functions of these cell cycle inhibitors in five patientderived glioma stem cell?enriched cell lines. We found that these proteins are functional in glioma stem cells. They negatively regulate cell cycle progression both in unstressed conditions and in response to genotoxic stress. In addition, p27Kip1 is upregulated in nutrient-restricted and differentiating cells, suggesting that this Cip/Kip is a mediator of antimitogenic signals in glioma cells. Importantly, the lack of these proteins impairs cell cycle halt in response togenotoxic agents, rendering cells more vulnerable to DNA damage. For these reasons, these proteins may operate both as tumor suppressors, limiting cell proliferation, and as oncogenes, conferring cell resistance to DNA damage.Thus, deepening our knowledge on the biological functions of these Cip/Kipsmay shed light on howsomecancer cells develop drug resistance.